2018
DOI: 10.4172/2329-9029.1000224
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Sugars in Plants Under Stress at the Arabian Gulf Region: Possible Roles of Microorganisms

Abstract: This review discusses the functions of soluble sugars (as compatible solutes) in supporting the growth of plants under osmotic stress, and the perspectives of research on the role of the associated microorganisms as a new approach in providing these solutes to plants. Previous findings have suggested that plants sacrifice from their energy and reserves to build up compatible solutes and to perform various functions; as osmo-protectants and possibly to stabilize biomolecules, and to achieve osmotic adjustment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…They serve as metabolic precursors for other metabolites or together with other metabolites, such as GABA or polyamines, may act as signalling molecules, controlling the gene expression in various metabolic pathways [25]. Yasseen et al [26] concluded that sugars can contribute to about 30–50% of the osmotic adjustment in the leaves of many glycophytes. In the present work, we found that sugar accumulation also depended on the nature of the osmotica.…”
Section: Discussionmentioning
confidence: 99%
“…They serve as metabolic precursors for other metabolites or together with other metabolites, such as GABA or polyamines, may act as signalling molecules, controlling the gene expression in various metabolic pathways [25]. Yasseen et al [26] concluded that sugars can contribute to about 30–50% of the osmotic adjustment in the leaves of many glycophytes. In the present work, we found that sugar accumulation also depended on the nature of the osmotica.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, most root exudates are of antimicrobial actions and might boost many activities related to growth under extreme environmental conditions (Huck et al, 1991;Walker et al, 2003;Srividya et al, 2008;Ahmed et al, 2013;Bizuye et al, 2013). Researchers should now conduct comprehensive investigations to explore the reality of the role of microbes at the rhizosphere, including contributions to resisting extreme biotic and abiotic factors (Glick, 2014;Hanin et al, 2016;Yasseen, 2018a,b, 2021;Yasseen et al, 2018).…”
Section: Coastal Areas and Sabkhasmentioning
confidence: 99%
“…During the last decade, great efforts have been made to draw attention to potential contributions of microorganisms to solving the many problems facing humans (Glick, 2012(Glick, , 2014Hanin et al, 2016;Al-Thani and Yasseen, 2018bYasseen et al, 2018). Moreover, some recent works [e.g., Egamberdievea et al (2017) and Yan et al (2020)] have suggested that rootassociated microbes offer some support to the growth of plants by producing phytohormones against abiotic stresses .…”
Section: Sand Dunesmentioning
confidence: 99%
See 1 more Smart Citation